“Jogo Tonggo” Efektivitas Kearifan Lokal; Solusi Pandemi Covid-19 - Muh Fajar Shodiq (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
The Covid-19 pandemic has entered its 2nd year. This epidemic hit all aspects of people's lives, from the aspects of health, education, tourism, economy, social, culture, politics to 'changing' civilization. Various ways have been taken by various parties to be able to remain healthy and still be able to